Remarks at Education Conference, Brussels, May 2, 2007 - Wolfowitz, Paul (World Bank, Washington, DC, 2019)
Paul Wolfowitz, President of the World Bank, spoke about Education for All being at the forefront of the development agenda. He spoke about four pillars to improve the education: (i) More aid: Education for all; (ii) Better aid: Quality of education that ensure the financial resources to align behind developing countries polices and strategies; (iii) Faster aid: New aid instruments and aid delivery mechanisms need to be used to ensure that resources are channeled fast to the local levels, where they are most needed; and (iv) Long-term predictable aid: Developing countries cannot develop comprehensive sector-wide strategies without being able to rely on foreign aid for more than 2 or 3 years. Moving forward, the World Bank will continue to expand our support for countries with good policies and help them build capacity.